Utilization, satisfaction, out of pocket expenditure and health seeking behaviour among the insured residents of rural field area: a cross sectional study - G., Netra; Rao, B. A. Varadaraja; Kengnal, Prakash (International Journal Of Community Medicine And Public Health, 2020)
Background: Health insurance is also called as medical insurance offering coverage that pays for unexpected medical and surgical expenses to the policyholder. A health insurance plan is one of the most secured and safest way to provide financial coverage to the insured family. Objective of this study was to assess utilization, satisfaction, out of pocket expenses and to determine the health seeking behaviour of the insured residents of the rural field practice area of SSIMS and RC, Davanagere. Methods: The study was done in the rural field practice area of the medical college, Davangere from January 2016 to December 2016. A sample of 600 families were studied by systematic random sampling and data was collected from the head of the family using structured questionnaire by house to house interview. Statistical analysis was carried out by SPSS v10, percentages, proportions and Chi-square tests were applied to find the association among the variables. Results: The utilization of health insurance in the present study was 50.2% and satisfaction regarding the health insurance schemes was 93.4%. Conclusions: The study reveals that the out of pocket expenses is high among the uninsured families compared to the insured families. The Insurance policies should be revived to do favour the patients so that more families will be encouraged to enrol and utilize so that the out of pocket expenses will be reduced.